Social Capital and Household Vulnerability of Fishermen’s Household in Lae-Lae Island, Makassar City - Irwansyah Idrus, Idham; Tamrin, Sopian; Amandaria, Riri; Isma, Ashari (KnE Social Sciences, 2024)
The results of research conducted in 2022 in the Lae-Lae Island fishing community found that the forms of household livelihood vulnerability can be categorized into: pressure from external community factors that are long-term and broad-scale (trends), shocks that come in a short time that disrupt sources of livelihood, and disturbances or pressures that are seasonal. The study also found that small-scale fishing communities carry out three livelihood strategies namely: (1) double income pattern; (2) optimizing the role of the family; and (3) utilizing social networks. The factors of the existence of physical and financial capital as an essential element of resilience show that these two capitals still need to be improved in the community’s possession. This research is a continuation of previous research, aiming to determine the strength of social capital possessed by fishing communities in dealing with household livelihood vulnerabilities on Lae-lae Island, Makassar City. This type of research is descriptive qualitative with informants and was carried out through purposive sampling. Researchers used observation data collection techniques, interviews, and documentation. The analysis technique used is qualitative data analysis and is descriptive. The study found that social norms in the fishing community on Lae-lae Island contributed to other elements of social capital. Social solid norms maintain the habit of mutual assistance, high trust among them, and cooperation built in a network of social and institutional relations, which is a condition rooted in the socio-cultural values of the fishing community of the Bugis-Makassar tribe. Keywords: social capital, resilient, livelihood strategy